EKSPERIMENTASI MODEL PEMBELAJARAN DISCOVERY LEARNING, GROUP INVESTIGATION, DAN THINK TALK WRITE DENGAN PENDEKATAN SAINTIFIK TERHADAP PRESTASI DAN KREATIVITAS BELAJAR MATEMATIKA PADA MATERI BANGUN RUANG SISI DATAR DITINJAU DARI KEMAMPUAN PENALARAN SISWA - Nuraya, Naufalia; Mardiyana, Mardiyana; Slamet, Isnandar (Jurnal Pembelajaran Matematika, 2015)
Abstract: This research aims to know the different effect among learning models used i.e, Discovery Learning (DL) with scientific approach, Group Investigation (GI) with scientific approach, and Think Talk Write (TTW) with scientific approach. The research method was quasi experimental. The population was all students of grade VIII State Junior High School of district Tegal year of 2014/2015. Sample was taken by stratified cluster random sampling technique. The hypothesis test used two way MANOVA with unbalanced cell. The results of the research were as follows: (1) a. Learning achievement of students treated by DL with scientific approach is better than those treated by GI and TTW with scientific approach, and learning achievement of student treated by GI with scientific approach is the same good with student treated by TTW with scientific approach; b. Mathematics learning creativity of student treated by DL and GI with scientific approach is better than those treated by TTW with scientific approach, and mathematics learning creativity of student treated by DL with scientific approach is the same good with student treated by GI with scientific approach; (2) a. Learning achievement of students who have high and medium reasoning ability is better than those who have low reasoning ability, and learning achievement of students who have high reasoning ability is the same good with students who have medium reasoning ability; b. Mathematics learning creativity of students who have high and medium reasoning ability is better than those who have low reasoning ability, and mathematics learning creativity of students who have high reasoning ability is the same good with students who have medium reasoning ability; (3) a. In the high, medium, and low reasoning ability, learning achievement of students treated by DL with scientific approach is better than those treated by GI and TTW with scientific approach, and learning creativity of student treated by GI with scientific approach is the same good with student treated by TTW with scientific approach; b. In the high, medium, and low reasoning ability, mathematics learning creativity of students treated by DL and GI with scientific approach is better than those treated by TTW with scientific approach, and learning creativity of students treated by DL with scientific approach is the same good with student treated by GI with scientific approach; (4) a. In DL, GI, and TTW with scientific approach, learning achievement of students who have high and medium reasoning ability is better than those who have low reasoning ability, and learning achievement of students who have high reasoning ability is the same good with students who have medium reasoning ability; b. In DL, GI, and TTW with scientific approach, mathematics learning creativity of students who have high and medium reasoning ability is better than those who have low reasoning ability, and mathematics learning creativity of students who have high reasoning ability is the same good with students who have medium reasoning ability.Keywords: DL, GI, TTW, Scientific Approach, Reasoning Ability, Learning Achievement, Mathematics Learning Creativity.